ANALYSIS OF THE EFFECT OF CREDIT RESTRUCTURING, NIM, AND CKPN ON NPL (2020–2024) - Sri Nur Fadhilah; Muhammad Zilal Hamzah; Giri Tri Broto (Media Ekonomi, 2025)
This study aims to analyze the effect of credit restructuring, NIM, and CKPN on NPLs at commercial banks in Indonesia during the 2020–2024 period by comparing the Covid-19 and post-Covid-19 periods. The study used a quantitative approach. The independent variables include credit restructuring, Net Interest Margin (NIM), and Allowance for Impairment Losses (AIL), while the dependent variable is Non-Performing Loans (NPL). The data used is secondary panel data from the financial reports of 10 commercial banks for the period 2020–2024, which is analyzed using panel data regress. The results show that credit restructuring played a role in suppressing the increase in NPLs during the pandemic, but its effectiveness declined in the post-pandemic period. NIM and CKPN were found to have an impact on NPLs and to be important factors in credit risk management and banking performance stability.